KESIAPAN GURU EKONOMI TERHADAP 9 PERUBAHAN KURIKULUM 2013 REVISI 2017 DI SMAN 9 PONTIANAK - Laras, Laras; Purwaningsih, Endang; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCurriculum is the foundation for educators and education personnel to achieve the goals set. The curriculum that is implemented in Indonesia so it requires teachers to be ready for implementation. Especially now that the 2013 revised curriculumÂ has been implemented in 2017 which result in several revisions, whichÂ are important points for teachers to know. This study aims ti find out how the readiness of economic subject teachers on 9 revised curriculum changes in 2017 in Pontianak 9 Public High School. The method used is descriptive with qualitative research forms. Data sources in this study are primary and secondary. The results of the study showed the readiness of economic subject teachers on 9 revised curriculumÂ changes in 2017 in Pontianak 9 SMA Negeri related to changes in curriculum name, changes in KI-1 and KI-2 attitudes assessment, changes in practice and skill assessement, 5M scientific approach, syllabus changes, change in terninology, changes in RPP, changes in rating scale, and remedial provision has gone well. Keywords: Readiness, Economics Teacher, 9 Revised 2013 Curriculum Changes